OPTIMALISASI KAPASITAS DAYA MELALUI UPRATING RUNNER TURBIN PADA PLTA PLENGAN - Fadli Kurnia; Dhany Hermeidy Barus (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
The Plengan Hydroelectric Power Plant is located in Pulosari Village, Pangalengan District, Bandung Regency, West Java. There are 5 hydro power plants still operating under the Plengan Hydroelectric Power Plant. The current problem lies in unit 5, which is a relocation unit from the Susukan Hydroelectric Power Plant with an installed capacity of 1600 kW. The performance of this unit has decreased so that it is only able to produce 1000 kW of power. This is suspected to be due to the specifications of the installed turbine not being in accordance with the actual conditions in the new location, especially in the head and water discharge parameters. This study aims to improve the efficiency of the power plant through the reverse engineering process and Computational Fluid Dynamics (CFD) simulation to uprate the turbine runner. The results of the design and simulation show that the efficiency has increased from 62% to 90% so that the output power can be increased to 1600 kW with an operating discharge parameter of 2.07 m³/s. From a financial perspective, it increases annual revenue from 3.15 billion to 4,7 billion with cheaper production costs than third parties. This study shows that optimizing turbine design based on actual data can significantly improve the efficiency and performance of the power plant unit.